The Far Edges of the Fourth Genre : An Anthology of Explorations in Creative Nonfiction - Wilkins, Joe; Prentiss, Sean, 1972- (Book collections on Project MUSE., 2014)
Overview: Though creative nonfiction has been around since Montaigne, St. Augustine, and Seneca, we've only just begun to ask how this genre works, why it functions the way it does, and where its borders reside. But for each question we ask, another five or ten questions roil to the surface. And each of these questions, it seems, requires a more convoluted series of answers. What's more, the questions students of creative nonfiction are drawn to during class discussions, the ones they argue the longest and loudest, are the same ideas debated by their professors in the hallways and at the corner bar. In this collection, sixteen essential contemporary creative nonfiction writers reflect on whatever far, dark edge of the genre they find themselves most drawn to. The result is this fascinating anthology that wonders at the historical and contemporary borderlands between fiction and nonfiction; the illusion of time on the page; the mythology of memory; poetry, process, and the use of received forms; the impact of technology on our writerly lives; immersive research and the power of witness; a chronology and collage; and what we write and why we write.